2013
DOI: 10.1371/journal.ppat.1003109
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Exchange between Borrelia burgdorferi and Host Cells

Abstract: Borrelia burgdorferi, the agent of Lyme disease, has cholesterol and cholesterol-glycolipids that are essential for bacterial fitness, are antigenic, and could be important in mediating interactions with cells of the eukaryotic host. We show that the spirochetes can acquire cholesterol from plasma membranes of epithelial cells. In addition, through fluorescent and confocal microscopy combined with biochemical approaches, we demonstrated that B. burgdorferi labeled with the fluorescent cholesterol analog BODIPY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
114
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(116 citation statements)
references
References 92 publications
1
114
0
1
Order By: Relevance
“…In contrast, the remainder of the culture filtrate after depletion of MV by ultracentrifugation contained much less LpqH and SodC, and the levels of these proteins in the soluble fraction were comparable in the two strains. To detect MV released into the culture fluid, we used the lipophilic probe, 1,6-diphenyl-1,3,5-hexatriene (DPH), which fluoresces in hydrophobic environments but not in aqueous environments (32) and has been used to detect MV in Borrelia burgdorferi culture supernatants (33). By the DPH assay, VirR-deficient Mtb released 1.5-fold more lipid than WT Mtb, whereas the complemented strain released less than half as much as WT (Fig.…”
Section: Virr Regulates Release Of Immunomodulatory Factorsmentioning
confidence: 99%
“…In contrast, the remainder of the culture filtrate after depletion of MV by ultracentrifugation contained much less LpqH and SodC, and the levels of these proteins in the soluble fraction were comparable in the two strains. To detect MV released into the culture fluid, we used the lipophilic probe, 1,6-diphenyl-1,3,5-hexatriene (DPH), which fluoresces in hydrophobic environments but not in aqueous environments (32) and has been used to detect MV in Borrelia burgdorferi culture supernatants (33). By the DPH assay, VirR-deficient Mtb released 1.5-fold more lipid than WT Mtb, whereas the complemented strain released less than half as much as WT (Fig.…”
Section: Virr Regulates Release Of Immunomodulatory Factorsmentioning
confidence: 99%
“…Recently, we demonstrated that B. burgdorferi acquires cholesterol from host cells (21). Cholesterol can remain free in the membrane or can be internalized and glycosylated by undetermined enzymes (22).…”
mentioning
confidence: 99%
“…Recently, a spate of studies on the regulatory networks of B. burgdorferi have added several layers of complexity to the molecular mechanisms that connect external signal recognition to appropriate host-specific adaptation in its disparate hosts (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Expression of several key lipoproteins of B. burgdorferi such as outer surface protein C (OspC) and decorin binding proteins A and B (DbpA/B) that contribute to vertebrate host infection were shown to be dependent on the Rrp2-RpoN-RpoS pathway (20)(21)(22)(23).…”
mentioning
confidence: 99%